Skrining dan Identifikasi Bakteri Laut dalam Yang Berasosiasi dengan Sampah Plastik Laut Berpotensi Mendegradasi Plastik Polyethylene (PE) - Karisma Isrami Brillianta Dyar (Fakultas Teknik, 2026)
Polyethylene (PE) is one of the most widely produced plastics and a major contributor to marine pollution due to its high resistance to natural degradation. In marine environments, plastic debris can serve as a substrate for microbial colonization, forming the plastisphere, and gradually fragment into microplastics that pose risks to ecosystems and human health. Biodegradation using deep-sea bacteria represents a promising and environmentally sustainable approach, given their ability to adapt to extreme conditions and utilize limited carbon sources. This study aimed to screen and identify deep-sea bacteria associated with marine plastic waste with potential for polyethylene degradation. A total of 135 bacterial isolates were obtained, of which 52 exhibited initial degradation potential, and 43 produced clear zones on Mineral Salt Medium (MSM) supplemented with polyethylene glycol (PEG). Enzymatic screening using Remazol Brilliant Blue R (RBBR) and guaiacol showed no detectable ligninolytic activity. Five selected isolates were further evaluated using DCPIP and n-hexadecane, where four isolates demonstrated positive oxidation activity. Phenotypic characterization revealed that the isolates were Gram-positive, with colony pigmentation ranging from yellow to brown. Isolate MBAC24-PL-001 exhibited the highest overall activity and was selected for molecular identification. Analysis of the 16S rRNA gene indicated a close affiliation with a deep-sea bacterial genus associated with hydrocarbon degradation. These findings highlight the potential of deep-sea plastisphere-associated bacteria as candidates for polyethylene biodegradation.
:: Finalisasi file repositori 4 Agustus 2026_Kurnadi
Keywords: polyethylene; deep-sea bacteria; biodegradation; plastisphere; marine pollution